2019
DOI: 10.1002/ecy.2634
|View full text |Cite
|
Sign up to set email alerts
|

Landscape context explains ecosystem multifunctionality in restored grasslands better than plant diversity

Abstract: There is strong evidence for a positive relationship between biodiversity and ecosystem functioning at local spatial scales. However, how different aspects of biodiversity relate to multiple ecosystem functions (multifunctionality) across heterogeneous landscapes, and how the magnitude of biodiversity, dominant species, and environmental effects on functioning compare, remain poorly understood. We compared relationships between plant phylogenetic, functional, and taxonomic diversity and ecosystem multifunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 62 publications
(186 reference statements)
3
53
0
Order By: Relevance
“…For example, wood biomass and non-timber forest products cannot be simultaneously increased in Swedish forests (Gamfeldt et al, 2013). In addition, ecosystem multifunctionality may be driven by different individual functions that respond strongly to diversity or environmental conditions or by all functions increasing together (Zirbel, Grman, Bassett, & Brudvig, 2019). Thus, identifying how different ecosystem functions respond to biodiversity and environmental conditions, as well as their relative contributions to multifunctionality, is critical to formulating sustainable management and conservation policies (Baeten et al, 2018;Felipe-Lucia et al, 2018; van der Plas, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, wood biomass and non-timber forest products cannot be simultaneously increased in Swedish forests (Gamfeldt et al, 2013). In addition, ecosystem multifunctionality may be driven by different individual functions that respond strongly to diversity or environmental conditions or by all functions increasing together (Zirbel, Grman, Bassett, & Brudvig, 2019). Thus, identifying how different ecosystem functions respond to biodiversity and environmental conditions, as well as their relative contributions to multifunctionality, is critical to formulating sustainable management and conservation policies (Baeten et al, 2018;Felipe-Lucia et al, 2018; van der Plas, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic diversity, the strongest expected predictor of EMF, was not significantly related to EMF, perhaps because the phylogenetic signal of functional traits related to each EF might not always be present (Davies et al 2016). Zirbel et al (2019) suggested that if the functional traits that determined an EF were not phylogenetically conserved, phylogenetic diversity might not be a good predictor of that EF. We suspected that some species, functional traits, and phylogenetic signals were lost during thinning.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists pointed out that species richness was not a particularly good metric for biodiversity because species richness does not provide direct information about traits like functional or phylogenetic diversity does (Gamfeldt and Roger 2017;Zirbel et al 2019). Functional diversity might be a better predictor of ecosystem function or multifunctionality (Díaz and Cabido 2001;Gross et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic diversity, supposed to be the most expected predictor of EMF, was not signi cantly related to EMF, perhaps because the phylogenetic signal of functional traits related to each ecosystem function might not always be present (Davies et al 2016). Zirbel et al (2019) suggested that if the functional traits that determined an ecosystem function were not phylogenetically conserved, phylogenetic diversity might not be a good predictor of that ecosystem function. We concluded that some species, functional traits, and phylogenetic signals were lost during logging.…”
Section: Discussionmentioning
confidence: 99%
“…species richness as a metric of biodiversity, since it is a simple metric to study and could be extended to other diversity metrics (Isbell et al 2011;Maestre et al 2012;Gamfeldt and Roger 2017). Scientists pointed out that species richness was not a particularly good metric for biodiversity because species richness does not provide direct information about traits like functional or phylogenetic diversity does (Gamfeldt and Roger 2017;Zirbel et al 2019). Plant functional traits are the characteristics of morphological, phenological and physiological, which could re ect how plants respond to environmental changes, and in uence other trophic levels and different ecosystem processes (Pérez-Harguindeguy et al 2013).…”
Section: Introductionmentioning
confidence: 99%